Design and Optimal Location of Power System Stabilizer in the Multi-Machine Power Network - Kumar R.; Mohanty S.R.; Verma M.K. (My University, 2025)
This paper proposes a damping torque index (DTI) to determine the optimal installation location of the power system stabilizer (PSS) in the multi-machine power network. The proposed index is based on the classical damping torque analysis (CDTA) method for power system low-frequency electro-mechanical (LFEO) analysis. The selection criteria of the PSS location is the maximum magnitude of DTI under normal operating conditions. The CDTA method is used to design PSS, and the phase compensation technique subsequently adjusts the associated parameters. Furthermore, to analyze the power system’s critical oscillation mode, a wide-area damping controller (WADC) is design for the synchronous generator where optimal location of PSS is install. The reduced-order model-based WADC includes time-varying delay in the wide-area signal. The WADC’s input signals from the phasor measurement unit (PMU) and the location of the PMU are selected using geometric measures of observability and WADC parameters design based on the residue approach. The proposed approach is validated in two separate test systems, and modal analysis is carried out on MATLAB software. The simulated results have been validated on the real-time digital simulator (RTDS) RSCAD 5.012. Results obtained on RTDS show that the proposed approach efficiently damps low-frequency electro-mechanical oscillations. © 2024 IETE.